Marine Tourism Event Concept at Minang Rua Beach, Kelawi Tourism Village, South Lampung - Helidatasa Utami; Damara Saputra Siregar; Gita Hilmi Prakoso; Arifin; Emirullyta Harda Ninggar (Journal of Tourism Sustainability, 2025)
This study examines the strategic development of marine tourism events through an integrated analytical and planning framework at Minang Rua Beach, Kelawi Tourism Village, South Lampung. Employing a descriptive qualitative design, the research synthesises field observations and semi-structured interviews, along with SWOT and GAP analyses, to evaluate destination readiness and identify critical determinants shaping event feasibility. The findings reveal that Minang Rua Beach benefits from strong accessibility, diverse natural and cultural assets, active community support, and the presence of indigenous knowledge systems. Nevertheless, several structural constraints persist, including limited engagement from governmental and private-sector stakeholders, suboptimal management of tourism attractions, and inadequate development of cultural arts and MSME branding. The GAP assessment indicates an overall readiness level of 87.5%, reflecting a generally favourable baseline with a measurable scope for improvement. Drawing on Goldblatt’s five-phase event planning model—research, design, planning, coordination, and evaluation—the study proposes a contextually grounded event development framework that emphasises enhancing destination quality, cultural revitalisation, human capital empowerment, and MSME advancement. Conceptually, this research contributes to the growing body of literature on event-based coastal tourism by demonstrating how strategic analytical tools can be operationalised within community-based governance structures to strengthen sustainable marine tourism development.